1-Cyclohexyl-5-(4-methoxyphenyl)-1H-pyrazole-4-carboxylic acid - Fun, Hoong-Kun (International Union of Crystallography, 2011)
In the title compound, C(17)H(20)N(2)O(3), the methoxyphenyl unit is disordered over two sets of sites in a 0.715 (4):0.285 (4) ratio. The pyrazole ring forms dihedral angles of 55.88 (16) and 72.6 (4)° with the benzene rings of its major and minor components, respectively. The cyclohexane ring adopts a chair conformation and its C—N bond is in an equatorial orientation. In the crystal, molecules are linked into inversion dimers by pairs of O—H⋯O hydrogen bonds, generating R (2) (2)(8) loops.